2006
DOI: 10.1177/0361198106196800102
|View full text |Cite
|
Sign up to set email alerts
|

Travel Time Estimation with Correlation Analysis of Single Loop Detector Data

Abstract: In this paper, the average travel time over a link is considered as a random variable following an identical probability distribution as the arrival process. A new estimation method of the average travel time uses a cross-correlation analysis of traffic flow measurement data. This method requires only traffic flow information, which is available from the measurements of single loop detectors upstream and downstream from one link. Different from the existing maximum cross-correlation analysis method, the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…An incident should extend the time in which the vehicles cover the distance between the upstream and downstream detector due to the obstruction, which implies an incident. The speed of a vehicle can be detected using single inductive loop at junction entries and exits, correlation analysis of traffic volume on the inductive loop (Guo, 2006) or advanced algorithms that allows the re-identification of the vehicle on the junction by using its electric signature from the inductive loop (Sun, 2004). The average value for the total number of vehicles passing through the junction can be calculated by treating all upstream detectors as one entry detector and all downstream detectors as one exit detector.…”
Section: Microscopic Simulation Of Incident Detection At Junctionsmentioning
confidence: 99%
“…An incident should extend the time in which the vehicles cover the distance between the upstream and downstream detector due to the obstruction, which implies an incident. The speed of a vehicle can be detected using single inductive loop at junction entries and exits, correlation analysis of traffic volume on the inductive loop (Guo, 2006) or advanced algorithms that allows the re-identification of the vehicle on the junction by using its electric signature from the inductive loop (Sun, 2004). The average value for the total number of vehicles passing through the junction can be calculated by treating all upstream detectors as one entry detector and all downstream detectors as one exit detector.…”
Section: Microscopic Simulation Of Incident Detection At Junctionsmentioning
confidence: 99%
“…Essas técnicas geram dados sintéticos, que podem ser velocidades ou tempos de viagem (Petty et al, 1998;Lin et al, 2004;Jeong e Rilett, 2005;Guo e Jin, 2006;Oh e Chung, 2006;Emam e Al-Deek, 2006) ou ainda matrizes OD (Gajewski et al, 2002;Park et al, 2008). Diversos estudos usam dados gerados por simulação para complementar dados coletados em campo (Schultz, 2003;Gomes, 2004) ou até para substituí-los (Araújo e Setti, 2008).…”
Section: Introductionunclassified
“…The methods range from simple regression analyses and cross correlation analyses (Dailey 2003), to more complicated probabilistic regression models (Petty et al 1998;Zhang et al 1999;Guo and Jin 2006). developed two regression models to estimate travel time: one for freeways with a permanent bottleneck, and another for freeways with a temporary downstream bottleneck.…”
Section: Statistical Approachmentioning
confidence: 99%
“…The case study showed that this method can estimate travel time even during very congested conditions. Later, extensions of this method include using the B-splines, exponential moving (Zhang et al 1999), and correlation analysis (Guo and Jin 2006) to improve the estimation of the probability density function.…”
Section: Statistical Approachmentioning
confidence: 99%
See 1 more Smart Citation